PEDAGOGICAL FOUNDATIONS OF USING ARTIFICIAL INTELLIGENCE IN TEACHING CHEMISTRY - Ajieva, Muxabbat Baxtibaevna; Arislanbaeva, Nesibeli Nokisbaevna; Sultanov, Dastonbek Kutlimurodovich (SCIENCE and SOCIETY, 2026)
The article discusses the current issues of using artificial intelligence technologies in the modern higher education system. In particular, the didactic capabilities of digital tools based on artificial intelligence in the process of teaching chemistry, their importance in increasing educational efficiency, and their role in developing professional competencies of future chemistry teachers are scientifically and theoretically analyzed.
Keywords: artificial intelligence; higher education; chemistry education; digital pedagogy; virtual laboratory; adaptive learning